Zgodovinska kartografija ozemlja Slovenije - Gašperič, Primož (Geografija Slovenije, 2022)
The book ('Historical cartography of Slovenian territory') presents the history of cartographic development in Europe and Slovenian territory with a special emphasis on a uniform methodology of studying old maps. The introduction provides definitions of the basic cartographic terminology and discusses the importance of maps, their study, and the development of European cartography from its beginnings to the twentieth century. This is followed by a presentation of cartographic elements and their classification into five basic groups (i.e., natural, built, mathematical, and explanatory elements plus geographical names), and an analysis of their historical development. The main part of the volume presents the methodology for studying cartographic elements and the results of an analysis of fifty-eight medium-scale maps of what is now Slovenia from the mid-sixteenth century to the end of the nineteenth century. A list of basic information on the most important maps of Slovenian territory is added at the end as an appendix. Maps can serve as the basis for exploring and studying landscapes and their processes. Old maps provide original information and are thus considered primary historical sources. The methodology used in this volume makes it possible to study these primary sources in a uniform manner across longer time periods.